Correlation studies on equity markets using linear regression model - Malaysia developing and developed markets - Haron, Razali; Zainal Abidin, Sazali; Larbani, Moussa (2006)
The specific objective of this paper is to generate and analyze the average correlation coefficient between Malaysian equity market and other selected countries equity markets during the period of 17 years from January 1987 to December 2003. The study employs Linear Regression Model to determine the correlation coefficients between Malaysia and other countries. The period of 17 years is further divided into 13 different sub-periods divided by pre, during and post crisis in order to study the differences in pattern of average correlation coefficient during the sub-periods. The study found that average correlations increase during the non crisis periods as compared to crisis periods. The study also divided the group of countries according to developed countries and emerging countries to analyze the correlation coefficients between Malaysian market and markets of those groups of countries. Malaysian market is found to be more correlated with the emerging market than the developed market. The study also analyzes the evolution of correlation of Malaysian market and other countries over time. The study concludes that there is a weak or no linear relationship on correlations between Malaysian market and foreign markets and time. This suggests that there is instability in market correlations over time. From an investment point of view of Malaysian investors,international portfolio diversification still offers diversification benefits due to instability in correlations over time.